Predicting the incidence of depression in adolescence using a sociodemographic risk score: Prospective follow-up of the IDEA-RiSCo study - Piccin, Jader; Buchweitz, Claudia; Manfro, Pedro H; Pereira, Rivka Barros; Rohrsetzer, Fernanda; Souza, Laila; Viduani, Anna; Caye, Arthur [UNESP]; Kohrt, Brandon A; Mondelli, Valeria; Swartz, Johnna R; Fisher, Helen L; et al. (BMJ, 2025)
Background Adolescence constitutes a critical window for preventing depression, but efforts have mostly targeted single risk factors. The Identifying Depression Early in Adolescence Risk Score (IDEA-RS) integrates easily obtainable sociodemographic variables and has been able to predict future depression across diverse populations. However, its performance within a prospective cohort remains untested. Objective To evaluate the performance of the IDEA-RS in a prospective sample of adolescents participating in the IDEA Risk Stratified Cohort. Methods Using the IDEA-RS, we screened 7720 adolescents aged 14-16 years in 101 public schools in Porto Alegre, Brazil, and recruited 50 low-risk (LR) and 50 high-risk (HR) participants without depression. The incidence of depressive disorders over 3 years was assessed using the Schedule for Affective Disorders and Schizophrenia for School-Age Children. Statistical analysis involved Poisson regression with robust variance to estimate incidence rate ratios (IRRs) for depression onset. Findings In the HR group, 14/45 developed depression, in comparison to 5/43 in the LR group. Poisson regression analysis confirmed a higher probability of developing depression in the HR group compared with the LR group (IRR of 2.68, 95% CI 1.05 to 6.79, p=0.04). Conclusion In a prospective cohort of Brazilian adolescents, the IDEA-RS effectively distinguished between those at HR and LR for developing depression. Clinical implications These results support the usefulness of an easy-to-administer sociodemographic composite risk score for stratifying the probability of developing depression among adolescents, a promising tool to be used in a variety of global contexts, including resource-limited settings.
Keywords: Child & adolescent psychiatry; Depression; Depression & mood disorders